Influência de partículas não-erodíveis com diferentes granulometrias na emissão em leitos e em pilhas de estocagem - Morais, Cristina Lima de (2018)
Emission of granular materials stored in stockpiles exposed to wind erosion is an important environmental issue currently discussed. One of the problematic cases are coal and iron ore particles due to the high fugitive emission potential during their handling and storage. Efforts have been made to create and test new models to estimate this type of emission, as in Caliman (2017) case. Caliman (2017) builded and validated the model using experiments with stockpiles composed of a binary mixture of erodible and non-erodible particles in two different proportions of non-erodible particles. As in nature the wind erosion processes occur in a wide range of diameters at various velocities, the present work aimed to investigate the influence of different non-erodible particle size distribution on beds and stockpile emission through the Caliman (2017) model. For the application of the model, some parameters were defined investigate the influence of different non-erodible particle size distribution on beds and stockpile emission through the Caliman (2017) model. In addition, an analysis of the evolution of the surface cover rate of the piles of the experiments used was performed to verify the behavior described in the literature. The results showed that the numerical simulations of the bed did not offer improvements in the modeled emission values. The relationship between the coverage rate and the eroded final height can still be considered linear for mixtures composed of different non-erodible granulometries with variable erodibility. Despite the errors, it is observed that the physical tendency of the erosion phenomenon was well modeled. The model has a physical basis both when it was created and when it was tested in the present work, requiring only deeper investigations of which, among the considerations made, propagated more errors. The analysis of the evolution of the surface cover rate of the experimental piles showed that the particle distribution can be partly explained, both qualitatively and quantitatively. However, not all phenomena can be visualized and included in the analysis.